(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2025)
This article explores the socio-political environment during Abu Hanifa’s lifetime and his stance toward political authority. It highlights his refusal to accept official positions, his respect for the Prophet’s descendants, and his major contributions to Islamic jurisprudence. Abu Hanifa’s legacy continues through the widespread Hanafi school of thought today. In particular, Abu Hanifa was offered the position of seal by Yazid ibn Umar during the Umayyad era and the position of judge in Baghdad by Caliph Abu Ja’far during the Abbasid era, but he declined the offers. The article also highlights the specific aspects of Abu Hanifa’s relationship with the judges of that era.